The Mediating Role of Job Satisfaction in Linking Organizational Culture and Self-Efficacy to Organizational Citizenship Behavior: A Study of Nurses in RSI Garam Kalianget Sumenep - Sanusi, Imam; Pratikto, Heri; Sopiah, Sopiah (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to analyze the influence of organizational culture and self-efficacy on organizational citizenship behavior with job satisfaction as a mediating variable among nurses at RSI Garam Kalianget Sumenep. The background is based on the importance of extra work behavior in improving the effectiveness of health services. The approach used is quantitative with descriptive and explanatory methods, as well as purposive sampling techniques with 114 respondents. Data analysis was conducted using SEM-PLS via SmartPLS 4.1.0.8. The results indicate that organizational culture and self-efficacy have a positive and significant effect on job satisfaction and organizational citizenship behavior. Job satisfaction was also found to significantly mediate this relationship. These findings underscore the important role of job satisfaction in encouraging voluntary employee behavior. The novelty of this research lies in testing an integrative model that simultaneously involves organizational culture, self-efficacy, job satisfaction, and organizational citizenship behavior, and was conducted in the context of a type C private hospital in an island region that has been rarely studied. This study also addresses inconsistencies in previous studies through a mediation approach. Practically, the results suggest that management should strengthen the internalization of organizational values through training and role modelling, and focus on enhancing self-efficacy and job satisfaction to promote organizational citizenship behavior that impacts service quality and hospital reputation.